The development of english vocabulary through the use of storytelling - Peñaloza Erreyes, John Alex; Mosquera Aguilar, Leidy Laura (Machala: Universidad Técnica de Machala, 2023)
The purpose of this research was to develop the English vocabulary of 4th grade A students at the 24 de Junio elementary school, through the implementation of a class system based on the use of Teaching Proficiency through Reading and Storytelling as a didactic strategy. Thus, the study was oriented in the quantitative paradigm with a descriptive pre- experimental design, making use of theoretical methods for the historical and conceptual foundation of the object of study, in addition to the application of empirical methods for data collection, through the use of instruments such as the observation guide, pedagogical test and teacher interview. As a result of the intervention, the data obtained from the post-test in contrast to the pre-test evidenced favorable changes in the knowledge of the study subjects, based on this it is concluded that the implementation of the TPRS strategy has a positive influence on the development of English language vocabulary.
La presente investigación tiene como finalidad desarrollar el vocabulario en inglés de los estudiantes de 4to A de la escuela de educación básica 24 de Junio, mediante la implementación de un sistema de clases basado en el uso de Teaching Proficiency through Reading and Storytelling como estrategia didáctica. Así mimo, el estudio se orientó en el paradigma cuantitativo con un diseño pre-experimental de tipo descriptivo, haciendo uso de métodos teóricos para la fundamentación histórica y conceptual del objeto de estudio, además de la aplicación de métodos empíricos para la recolección de datos, mediante el empleo de instrumentos tales como la guía de observación, prueba pedagógica y la entrevista dirigida al docente. Como resultado de la intervención del aporte práctico, los datos obtenidos del post test en contraste al pre-test evidenciaron cambios favorables en el conocimiento de los sujetos de estudio, en base a ello se concluye que la implementación de la estrategia TPRS tiene una influencia positiva en el desarrollo de vocabulario del idioma inglés.
Keywords: ENSEÑANZA-APRENDIZAJE; ESTRATEGIA DIDACTICA; DESARROLLO; VOCABULARIO